Does social thermal regulation constrain individual thermal tolerance in an ant species?. Issue 9 (23rd June 2020) - Villalta, Irene; Oms, Cristela Sánchez; Angulo, Elena; Molinas‐González, Carlos R.; Devers, Séverine; Cerdá, Xim; Boulay, Raphaël
Abstract: In ants, social thermal regulation is the collective maintenance of a nest temperature that is optimal for individual colony members. In the thermophilic ant Aphaenogaster iberica, two key behaviours regulate nest temperature: seasonal nest relocation and variable nest depth. Outside the nest, foragers must adapt their activity to avoid temperatures that exceed their thermal limits. It has been suggested that social thermal regulation constrains physiological and morphological thermal adaptations at the individual level. We tested this hypothesis by examining the foraging rhythms of six populations of A. iberica, which were found at different elevations (from 100 to 2, 000 m) in the Sierra Nevada mountain range of southern Spain. We tested the thermal resistance of individuals from these populations under controlled conditions. Janzen's climatic variability hypothesis (CVH) states that greater climatic variability should select for organisms with broader temperature tolerances. We found that the A . iberica population at 1, 300 m experienced the most extreme temperatures and that ants from this population had the highest heat tolerance (LT50 = 57.55°C). These results support CVH's validity at microclimatic scales, such as the one represented by the elevational gradient in this study. Aphaenogaster iberica maintains colony food intake levels across different elevations and mean daily temperatures by shifting its rhythm of activity. This efficient colony‐level thermal regulation and the significant differences in individual heat tolerance that we observed among the populations suggest that behaviourally controlled thermal regulation does not constrain individual physiological adaptations for coping with extreme temperatures. Abstract : This article presents a field study in a 100–2, 000 m elevational gradient of social and individual thermal regulation in an ant. It supports the climate variability hypothesis: the most thermally tolerant ants are those which experience the greatest thermal extremes at mid‐elevation sites. Colonies shifted foraging depending on temperature, resource acquisition did not vary across populations. Resumen: En hormigas, la termorregulación social es el mantenimiento colectivo de la temperatura del nido óptima para los individuos de la colonia. En la hormiga termófila Aphaenogaster iberica, hay dos comportamientos clave que regulan la temperatura del nido: la reubicación estacional y la profundidad variable del nido. Fuera del nido, las obreras recolectoras deben adaptar su actividad para evitar las temperaturas que excedan sus límites térmicos. Se ha sugerido que la termorregulación social limita las adaptaciones térmicas a nivel individual, fisiológicas y morfológicas. Examinamos esta hipótesis, estudiando los ritmos de actividad de recolección de alimento en seis poblaciones de A. iberica, a distinta altitud, desde 100 m a 2, 000 m, en las montañas de Sierra Nevada, en el sur de España. Y analizamos la resistencia térmica de los individuos de estas poblaciones, en condiciones controladas. La Hipótesis de la Variabilidad Climática de Janzen (CVH) postula que una mayor variabilidad climática selecciona organismos con tolerancias térmicas más amplias. Encontramos que la población de 1, 300 m era la que presentaba la mayor variabilidad climática, y que las hormigas de esta población tiene la mayor resistencia térmica individual (LT50 = 57.55°C), lo que confirma la validez de la CVH a una escala microclimática en el gradiente altitudinal estudiado. Encontramos que A. iberica puede compensar por la disminución de la temperatura media que acompaña al incremento en elevación. Las hormigas pueden cambiar sus ritmos de actividad sin afectar la entrada de alimento en la colonia, que tampoco se ve afectada por la elevación o la temperatura media diaria. A pesar de esta eficiente termorregulación a nivel de colonia, las diferencias estadísticamente significativas entre poblaciones observadas en la tolerancia térmica individual sugieren que la termorregulación controlada comportalmente no limita las adaptaciones fisiológicas individuales para enfrentarse a temperaturas extremas.